The impacts of irrigation and groundwater drainage induced salinity and overflooding of evaporation ponds in Khuzestan, Iran - Mao, Di; Riesbeck, Frank; Khodabakhshi, Hamid Reza; Mahjoobi, Arash (Frontiers in Water, 2025)
Salinity threatens agricultural productivity in Khuzestan, Iran, where irrigation and groundwater drainage exacerbate soil and water salinity. This study evaluates the impact of salinity and evaporation ponds on water management, focusing on the balance between discharge and inflow thresholds in a lagoon system. The study area in southwestern Khuzestan receives drainage from agriculture, industry, and fish farming. Groundwater discharge was estimated using hydrological models, and the lagoon’s inflow threshold was calculated based on evaporation rates adjusted for salinity. Data from 134 boreholes assessed groundwater depth and salinity. The result revealed that saline groundwater stays at a shallow level above the ground in the agricultural production area and is brought to the lagoon by the inappropriate layout of the drainage system, resulting in the phenomenon of over-flooding in the study area. The overall discharge flows at a rate of 84.63 m3/s compared to the inflow threshold of 21.17 m3/s, and the disequilibrium is mainly caused by unexpected saline groundwater and frequent exchanges of pond water in fish farms. The study highlights inefficiencies in water governance, particularly poor drainage system design and rapid fish farm expansion. Saline groundwater exacerbates soil salinity, reducing agricultural productivity. Improved salinity control, stricter regulations on fish farm water exchange, and enhanced groundwater management are essential for sustainable water resource management.